2021
DOI: 10.7860/ijars/2021/46607.2629
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Validity of Ultrasonography and Magnetic Resonance Imaging in Assessment of Uterine Adnexal Masses

Abstract: Introduction: Adnexal mass lesions are common among women which has a prevalence of 0.17%-5.9% in asymptomatic women and 7.1%-12% in symptomatic women of all ages. Making a differential diagnosis among adnexal masses is difficult and complex. Recognising the severity of the problem, appropriate and timely evaluation and treatment with good outcome is the goal. Aim: To find out the validity of Ultrasonography (USG) and Magnetic Resonance Imaging (MRI) in evaluation of uterine adnexal masses. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Their study showed serous cystadenoma as the most common benign lesion (31.2%). 6 Sultana N et al in their study showed high sensitivity and negative predictive values (100%, and 100%) for TAS for distinguishing benign and malignant lesions as compared to our study (63.15% and 92.3%). However, lower specificity and positive predictive values (54% and 58.8%) were recorded as compared to our study (95.5% and 75%).…”
Section: Discussioncontrasting
confidence: 45%
“…Their study showed serous cystadenoma as the most common benign lesion (31.2%). 6 Sultana N et al in their study showed high sensitivity and negative predictive values (100%, and 100%) for TAS for distinguishing benign and malignant lesions as compared to our study (63.15% and 92.3%). However, lower specificity and positive predictive values (54% and 58.8%) were recorded as compared to our study (95.5% and 75%).…”
Section: Discussioncontrasting
confidence: 45%
“…Sex cord-stromal tumors diagnosed were fibroma (5.71%) and fibro-thecoma (7.14%). In a study, Debbama et al found various benign adnexal masses such as dermoid, endometrioma, serous cystadenocarcinoma, Brenner tumor, hydrosalpinx, simple cyst, para-ovarian cyst, fibroma, endometriosis, and malignant masses like papillary cystadenocarcinoma, dysgerminoma, metastasis, granulosa cell tumor, adenocarcinoma, clear cell carcinoma, and immature teratoma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yashi et al noted in ten cases no septations were present in the lesion, of which nine (41%) were benign masses and one (4.5%) of malignant masses [9]. Adnexal mass lesions with thick septation, mural nodule, and intralesional vascularity on ultrasound were indicators of malignancy, according to Tanusri Debbarma et al [10].…”
Section: Discussionmentioning
confidence: 99%